Can't Get No Satisfaction? The Association Between Community Satisfaction and Population Size for Victoria. Issue 1 (20th January 2015) - Drew, Joseph; Dollery, Brian; Kortt, Michael A.
Abstract : Traditionally, the problem of determining the optimal size in local government has been empirically assessed by estimating the relationship between population size and the costs of services (usually measured in terms of per capita expenditure). These studies, however, have proved largely inconclusive. In comparison, an empirical analysis based on the relationship between the size of government and community satisfaction offers a potentially fruitful contribution to the debate regarding the optimal size of local government. However, to date, few studies have followed this approach. We therefore contribute to this literature by exploring the relationship between population size and community satisfaction for Victorian councils. Our findings provide evidence of an inverted 'U‐shaped' relationship, which predicts low community satisfaction at very large and very small population sizes. Abstract : While optimal size in local government has conventionally been determined by estimating the relationship between population size and expenditure, this approach has proved problematic. In this paper we develop an alternative approach which examines the relationship between population size and community satisfaction for Victorian councils and establishes an inverted 'U‐shaped' relationship.